Pathways to European greenhouse gas emissions trading history and misconceptions - Peter Zapfel; Matti Vainio (Fondazione Eni Enrico Mattei (FEEM), 2002)
We develop and discuss the three pathways to European Greenhouse Gas Emissions Trading: a top-down scheme based on the Kyoto Protocol of the UNFCCC, a bottom-up scheme linking national trading systems of EU Member States, and an EU-wide regional scheme based on the founding principles of the European Union. We review how the debate on greenhouse gas emissions trading has evolved in Europe since the adoption of the Kyoto Protocol in 1997 in three phases. We also review a set of influential misconceptions in the European discussion concerning emissions trading and, while dispelling them, try to establish why such misconceptions have arisen.
Keywords: D61; H23; Q25; 330; Climate policy; emissions trading; greenhouse gases; Kyoto Protocol; European Union; Klimaschutz; Umweltabkommen; Emissionshandel; Luftverschmutzung; Treibhausgas-Emissionen; EU-Staaten